Hazrat Azan Fakir: His Harmonious Message in “Zikir and Zȃrȋ” - Uddin Ahmed, Noor (International Journal of Psychosocial Rehabilitation, 2020)
Hazrat Azan Faqir came from Baghdad to Assam in the seventeenth century AD accompanied by his brother Nabi Shah with a view to spreading the message of Islam. He began to live first for a few years in the Khanqah of Giyath al-Dȋn Awliya, Hajo. It is 24 Kilometres northwest away from Guwahati. Then he lived at Chun Pora village for a long time, and finally at Saraguri Chapori, Sibsagar along with his 120 beloved disciples until his demise in 1690 AD. He preached the message of Islam to the Muslim people, who do not keep any difference from other religious adherents. So, Azan Fakir made them acquainted with the rituals of Islamic Sharia along with a harmonious message of Islam. In this connection, he composed “ Zikir and Zȃrȋ” in the form of Bargeet of Sankardeva. Here Zikir means remembrance of Allah i.e. saying prayers; while Jȃrȋ means remembrance of the martyrs who fought for Islam. In addition, his “ Zikir and Zȃrȋ” are endowed with the message of cultural harmony irrespective of caste and creed. In the passage of time, his Zikir and Zȃrȋ have been considered a distinct literary genre of Assamese literature. The message of Sufism also appears in the contents of his Zikir and Zȃrȋ and many Perso-Arabic words are available in their contents. In fact, he has been familiar as a legendary poet of Assam.